HUBUNGAN PERSEPSI GURU TERHADAP PERAN SUPERVISI KEPALA SEKOLAH DAN DISIPLIN KERJA DENGAN KINERJA GURU MADRASAH TSANAWIYAH NEGERI KOTA BOGOR - Najmulmunir, Nandang; Hasyim, Abd. Wahid; Jubaedah, Dedeh (Program Studi Magister Pendidikan Islam Universitas Islam 45, 2009)
The aim of this research is to know the correlation between teacher?s perception toward supervision of headmaster and work discipline with teacher?s performance in Madrasah Tsanawiyah Negeri Kota Bogor. The research method is using survey methods with respondent are from teachers in Madrasah Tsanwiyah Negeri Kota Bogor. The sample amounts are consisting of 60 samples. The samples pulling is using census. The hypothesis trial is done with significant result 0,05. The hypothesis significant result is show: (1). There is positive correlation which significant between teacher?s perception toward supervision of headmaster with teacher?s performance that show the coefficient correlation ry1=0,570 and the same regression Y =60,196+0,378X1 (2). There is positive correlation which significant between work discipline with teacher?s performance that shows the coefficient correlation ry2 = 0,463 and the same regression Y=53,591+0,419X2 (3). There is positive correlation which significant between teacher?s perception toward supervision of headmaster and work discipline with teacher?s performance that shows withthe coefficient correlation ry1.2 =0,618 and the same regression Y=42,027+0,301X1+0,240X2